Calcium channels: evidence for oligomeric nature by target size analysis. - Ferry, D R (1983)
Radiation inactivation was employed to measure the molecular size of calcium channels in guinea-pig skeletal muscle membranes, labelled by the potent 1,4-dihydropyridine calcium antagonist [3H]nimodipine. The molecular size was decreased when the membranes were preincubated and assayed with d-cis-diltiazem, a calcium channel blocker, which is structurally unrelated to the 1,4-dihydropyridines. d-cis-Diltiazem, which is a positive heterotropic regulator of 1,4-dihydropyridine calcium channel binding in vitro, reduced the molecular size from 178 000 to 111 500. 1-cis-Diltiazem, the diastereoisomer, which is devoid of calcium antagonistic action, did not decrease the molecular size of the 1,4-dihydropyridine binding site. Neither diastereoisomer affected the molecular size of the membrane-bound acetyl-cholinesterase, indicating that a stereospecific interaction with the calcium channel structure is the basis for these observations. It is concluded that this decrease in size is indicative of the oligomeric nature of the calcium channel and that calcium channel blockers, acting via different, but interacting drug receptor sites, induce different conformations of the channel structure, resulting in altered conductivity for ions.